Use of polyethylenimine to produce immobilized lipase multilayers biocatalysts with very high volumetric activity using octyl-agarose beads: Avoiding enzyme release during multilayer production - Peña, Sara Arana; Rios, Nathalia Saraiva; Sanchez, Carmen Mendez; Lokha, Yuliya; Gonçalves, Luciana Rocha Barros; Lafuente, Roberto Fernández (Enzyme and Microbial Technology, 2021)
A strategy to obtain biocatalysts formed by three enzyme layers has been designed using lipases A and B from Candida antarctica (CALA and CALB), the lipases from Rhizomucor miehei (RML) and Thermomyces lanuginosus (TLL), and the artificial chimeric phospholipase Lecitase Ultra (LEU). The enzymes were initially immobilized via interfacial activation on octyl-agarose beads, treated with polyethylenimine (PEI) and a new enzyme layer was immobilized on the octyl-enzyme-PEI composite by ion exchange, producing octyl-enzyme-PEI-enzyme biocatalysts. Except when using LEU, when the two-layer biocatalysts, a large percentage of the PEI-immobilized enzyme was released when a new batch of PEI was added. This was prevented by glutaraldehyde crosslinking. The enzyme modifications produced more active preparations in some cases while in other cases, the effect of the modifications was negative for enzyme activity. These effects of the enzymes modifications were also different when the enzyme was immobilized by interfacial activation or by ion exchange. In all cases, the 3-layer biocatalysts were more active than the single- or bi-layer biocatalysts with some of the assayed substrates. However, as the substrate diffusion problems increased when new enzyme layers were added, even a decrease in enzyme activity with some substrates was found after increasing the number of enzyme layers 2030-12